Pengembangan Sensor Getaran Dua Dimensi Menggunakan Sistem Sensor Fluxgate - Putra, Sandijal; Jannah, Raudhatul (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2018)
In this study, Fluxgate made with a design 30 and 20 winding excitation coil pickups. Fluxgate used to measure vibrations in two dimensions. Vibration measurements performed indirectly by using two mechanical pendulum to vibrate in the direction of axis x and y are placed on the source of vibration. Fluxgate sensor working principle is developed when there is vibration, then the magnetic mass at the end of the pendulum arm will come to move in rhythm with the vibration. This will result in the distance between the sensor with a magnetic mass changes. Changes in this distance will lead to changes in magnetic induction at the core of the sensor. Because of the large magnetic field intensity received by the sensor varies with the distance the vibration amplitude changes that occur will result in a change in voltage generated by the sensor. This means that the emf is happening is a function of the distance between the sensor with a magnetic mass. Fluxgate sensor is placed in the direction of axis x and y. Based on analysis of data obtained sensitivity of the sensor x and y with the same value that is Â± 39 mV / Î¼T. The range of frequencies that can be detected by sensors in this study were 0.37 Hz to 1.81 Hz and amplitude range that has been carried out ranging between 0.7 cm to 2.3 cm. Maximum absolute error and maximum relative error in the characterization of the frequency obtained is happening on the sensor y of 0.054 Hz and -2.18%. For amplitude obtained is happening on the sensor x 0,005 volt and 3,28%.